Respuesta :

Answer:

c (0,-4)

Step-by-step explanation:

-5x+y = -4

4x - 4y =16

Solve the first equation for y since we are using substitution.

-5x+y = -4

Add 5x to each side

-5x+5x+y = -4+5x

y = 5x-4

Substitute this equation y = 5x-4 into the second equation.

4x -4(5x-4) = 16

Distribute the -4

4x - 4(5x) -4(-4) = 16

4x-20x +16 = 16

Combine like terms

-16x +16 =16

Subtract 16 from each side

-16x+16-16 = 16-16

-16x =0

Divide by -16

x=0


But we still need to find y

y = 5x-4

y = 5(0) -4

y = -4

ACCESS MORE